TRACING THE HERITAGE AND CIVILIZATION OF AUSTRONESIAN SEAFARERS ACROSS WATERS, SEAS, AND OCEANS IN THE ARCHIPELAGO OF SOUTHEAST ASIA (Applied History Journal of Merong Mahawangsa, 2024)
The waters, seas and oceans have traditionally been a source of inspiration for the search for the truth. It also manages to negate the human worldview that associates it with various elements of myth and superstition. The waters, sea and oceans are also a place with the advantage of consolidating ties between countries, forming a united, mutual understanding and unity spirit and generating mutual wealth. It is an invaluable, irreplaceable and modified property. Historiography in Southeast Asia saw a close relationship between people named "humans‵‵ in the South China Sea, Sulu Sea, Sulawesi Sea, Flores Sea, Java Sea, Banda Sea and so on. History has shown how they have fought hard through various waves and storms in the seas and oceans simply to ensure that the next generation holds the souls of the sailors. It has made the region a centre of superior civilization as well as a model for the centers of other world civilizations. Therefore, this writing aims to reassess the history of the existence of the Austronesian seafarers from the perspective of the history in Southeast Asia   themselves. The results of this study have opened the enactment of whether it is true that the origin of this Austronesian seafarer’s tribe originated in Taiwan as stated in the theory of migration and linguistics. In other words, the Austronesian seafarer today come from Southeast Asia itself and have migrated out to expand their civilizations in regions of Oceania such as Polynesia, Melanesia, and Micronesia all the way to Taiwan up to Madagascar. There is no easy answer to this matter and need to study from various disciplines and space to find strong evidence of the Austronesian seafarers.